Aortoduodenal fistula - fatal complication in a patient with aortic prosthesis: Aortoduodenalna fistula - usoden zaplet pri bolniku z aortno protezo - Skok, Pavel (Acta Medico-Biotechnica, 2021)
Purpose: Aortoenteric fistula is an extremely rare source of upper gastrointestinal tract haemorrhage (UGIH).Case report: We present the case of a 58-year-old man who was admitted to our ward with UGIH. During diagnosis, urgent upper and lower GI endoscopy, abdominal US, CT angiography and ileojejunography were performed. Unfortunately, the bleeding source was not found and the patient was discharged. He returned 2 weeks later with profound anemia. Urgent upper GI endoscopy did not elucidate the bleeding source. The patient died suddenly a few days after receiving symptomatic treatment. At autopsy, a secondary aortoduodenal fistula due to prosthetic aortic reconstruction was found, which had led to fatal haemorrhage.Conclusion: Some sources of UGIH are very rare. In the diagnostic work up of these patients we should be aware of the limitations of different imaging procedures.
Keywords: aorto–enteric fistula; upper gastrointestinal haemorrhage; emergency endoscopy; exsanguination